Expression Profiles, Characterization and Function of HbTCTP in Rubber Tree (Hevea brasiliensis) - Deng, Zhi; Chen, Jiangshu; Leclercq, Julie; Zhou, Zhuangzhi; Liu, Changren; Liu, Hui; Yang, Hong; Montoro, Pascal; Xia, Zhihui; Li, Dejun (Frontiers in Plant Science, 2016)
As a highly conserved protein, the translationally controlled tumor protein (TCTP) carries out vital roles in various life processes. In rubber tree, two TCTP genes, HbTCTP and HbTCTP1, were cloned, but only HbTCTP1 was studied in details. In this study, cis-acting regulatory elements, expression patterns, subcellular localization, interacting proteins, and antioxidant activity of HbTCTP were systematically analyzed. Besides the common cis-acting regulatory elements, HbTCTP promoter also harbored various known cis-elements that respond to hormone/stresses. Being consistent with the aforementioned results, HbTCTP was regulated by drought, low temperature, high salt, ethylene (ET), wounding, H2O2, and methyl jasmonate (MeJA) treatments. HbTCTP was expressed throughout different tissues and developmental stages of leaves. In addition, HbTCTP was associated with tapping panel dryness (TPD). HbTCTP was localized in the membrane, cytoplasm and the nucleus, and interacted with four proteins rubber elongation factor (REF), 17.5 kDa heat shock family protein, annexin, and REF-like stress related protein 1. Being similar to HbTCTP1, HbTCTP also indicated antioxidant activity in metal-catalyzed oxidation (MCO) system. Our results are useful for further understanding the molecular characterization and expression profiles of HbTCTP, but also lay a solid foundation for elucidating the function of HbTCTP in rubber tree.